Dark-Induced Hormonal Regulation of Plant Growth and Development - Deepika,; Ankit,; Sagar, Sushma; Singh, Amarjeet (Frontiers in Plant Science, 2020)
The sessile nature of plants has made them extremely sensitive and flexible towards the constant flux of the surrounding environment, particularly light and dark. The light is perceived as a signal by specific receptors which further transduce the information through the signaling intermediates and effector proteins to modulate gene expression. Signal transduction induces changes in hormone levels that alters developmental, physiological and morphological processes. Importance of light for plants growth is well recognized, but a holistic understanding of key molecular and physiological changes governing plants development under dark is awaited. Here, we describe how darkness acts as a signal causing alteration in hormone levels and subsequent modulation of the gene regulatory network throughout plant life. The emphasis of this review is on dark mediated changes in plant hormones, regulation of signaling complex COP/DET/FUS and the transcription factors PIFs which affects developmental events such as apical hook development, elongated hypocotyls, photoperiodic flowering, shortened roots, and plastid development. Furthermore, the role of darkness in shade avoidance and senescence is discussed.